An observation‐based climatology and forecasts of winter fog in Ghaziabad, India. (January 2017) - Srivastava, Sanjay Kumar; Sharma, Anu Rani; Sachdeva, Kamna
Abstract : Long‐term ground observations of visibility and other meteorological parameters (for the period 1971–2010) have been analysed over Ghaziabad city, National Capital Region (NCR) to understand the formation of fog and its relevance during the winter months. The study reveals that the maximum frequency of fog occurs during December ( 23 days), followed by January ( 21 days), November ( 20 days), February ( 14 days) and October ( 11 days), respectively. In the last four decades, an increasing trend in fog frequency has been observed during the months of October to February over the study area. During the period of study, the frequency of fog has increased by 205.5% in the month of October and 50.2% in the month of November. Similar increasing trends have also been observed during the other winter months. A statistically significant increasing trend in fog occurrence has been observed between October and February during the study period at the 95% confidence level. The magnitude of the trend for each month is 0.50, 0.47, 0.30, 0.39 and 0.37 between October and February. Furthermore, the magnitude of the trend is greatest in the month of October, whereas the average monthly fog frequency is highest during the month of December. An attempt has also been made to forecast fog events using the ARIMA model over the study region. The forecast values obtained for five years into the future indicate that a further increase in the number of fog days is expected during the months of October to February. The study, combined with knowledge of meteorology and topography, suggests that, due to an increase in the availability of fine particulates and rapid urbanisation, fog formation may further increase in future and thus drastically disturb the social and economic activities across Ghaziabad, National Capital Region of India.